2000
DOI: 10.1054/bjoc.2000.1433
|View full text |Cite
|
Sign up to set email alerts
|

Production of a signal by irradiated cells which leads to a response in unirradiated cells characteristic of initiation of apoptosis

Abstract: Summary This study investigated the ability of medium from irradiated cells to induce early events in the apoptotic cascade, such as mobilization of intracellular calcium, loss of mitochondrial membrane potential and increase in reactive oxygen species, in cells which were never exposed to radiation. Medium from irradiated human keratinocytes was harvested and transferred to unirradiated keratinocytes. Endpoints characteristic of the initiation of apoptosis were monitored for a period of 24 h following medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(164 citation statements)
references
References 25 publications
(33 reference statements)
7
154
0
1
Order By: Relevance
“…Potentially related to the mechanisms mediating cytogenetic damage not requiring gap-junctional communication is the finding that the medium in which certain cells have been irradiated contains an activity, probably a protein, that produces cytotoxic effects in nonirradiated cells Lyng et al, 2000Lyng et al, , 2002Mothersill et al, 2000bMothersill et al, , 2001Seymour and Mothersill, 2000). The first detectable effect of the medium containing the cytotoxic activity on recipient cells is a rapid (1-2 min) calcium pulse followed 30 min-2 h later by changes in mitochondrial membrane permeability and the induction of ROS (Lyng et al, 2000(Lyng et al, , 2002; a role for mitochondrial metabolism is suggested by the lack of signal production by cells that lacked functional glucose-6-phosphate dehydrogenase (Mothersill et al, 2000b).…”
Section: Mechanisms Underlying Radiation-induced Bystander Effectsmentioning
confidence: 99%
“…Potentially related to the mechanisms mediating cytogenetic damage not requiring gap-junctional communication is the finding that the medium in which certain cells have been irradiated contains an activity, probably a protein, that produces cytotoxic effects in nonirradiated cells Lyng et al, 2000Lyng et al, , 2002Mothersill et al, 2000bMothersill et al, , 2001Seymour and Mothersill, 2000). The first detectable effect of the medium containing the cytotoxic activity on recipient cells is a rapid (1-2 min) calcium pulse followed 30 min-2 h later by changes in mitochondrial membrane permeability and the induction of ROS (Lyng et al, 2000(Lyng et al, , 2002; a role for mitochondrial metabolism is suggested by the lack of signal production by cells that lacked functional glucose-6-phosphate dehydrogenase (Mothersill et al, 2000b).…”
Section: Mechanisms Underlying Radiation-induced Bystander Effectsmentioning
confidence: 99%
“…These bystander-like interactions could involve the production of cytokines (Iyer and Lehnert, 2000) and/or free radical production (Lyng et al, 2000). Increased levels of reactive oxygen species in genomically unstable clones have been described (Clutton et al, 1996;Limoli et al, 1998Limoli et al, , 2001, and recently it was reported that X radiation caused a persistent induction of reactive oxygen species in normal human fibroblasts (Rugo et al, 2002).…”
Section: Implications Of Nontargeted Effectsmentioning
confidence: 99%
“…Those data clearly show that the protective effect was lost and transformation increased above control at doses between 100 and 300 mGy. Both protective bystander effects (Azzam et al, 1996;Broome et al, 2002) and detrimental bystander effects (Lyng et al, 2000;Seymour and Mothersill, 2000) have been shown to result from γ -radiation exposure at doses between 1 and 500 mGy. The data in Figure 2 therefore suggest the existence of a transition dose point between 100 and 300 mGy, below which protective effects, including protective bystander effects, predominate, and above which detrimental effects overwhelm the protective effects.…”
Section: Low Doses Bystander Effects and Risk In Vitromentioning
confidence: 99%